Značilnosti poezije osrednjih slovenskih pesnikov in pesnic, rojenih po letu 1970 - Bedrač, David (Slavia Centralis, 2020)
FEATURES IN POETRY OF THE MAIN SLOVENIAN POETS BORN AFTER 1970 This paper discusses sixty-one forms of poetics utilized by Slovenian poets born after 1970. The discussion presents some dominant features of this generation at the level of external and internal forms of poetic texts and encompasses key generational problems of poetry which stem from the relationship between autopoetics and dominant ideational tendencies. At the same time it provides a shorter refection of modern poetic texts viewed as a development and a conceptual continuum within Slovenian literary circles.